2011
DOI: 10.1074/jbc.m110.180893
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin Cholesterol Acyltransferase Null Mice Are Protected from Diet-induced Obesity and Insulin Resistance in a Gender-specific Manner through Multiple Pathways

Abstract: Here, we report that LCAT-deficient mice (DKO and Lcat) are protected against high fat high sucrose (HFHS) diet-induced obesity without hypophagia in a gender-specific manner compared with their respective (SKO and WT) controls. The metabolic phenotypes are more pronounced in the females. Changes in endoplasmic reticulum stress were examined as a possible mechanism for the metabolic protection. The female DKO mice developed attenuated HFHS-induced endoplasmic reticulum stress as evidenced by a lack of increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
1
42
1
2
Order By: Relevance
“…A positive relation between LCAT and obesity has been described (Sutherland et al. 1979) and LCAT-null mice have been shown to be protected from dietinduced obesity (Li et al, 2011). Therefore, the relative high level of LCAT in obese subjects may be responsible for clearance of specific PC species.…”
Section: Added Value Of Metabolomics Analysismentioning
confidence: 99%
“…A positive relation between LCAT and obesity has been described (Sutherland et al. 1979) and LCAT-null mice have been shown to be protected from dietinduced obesity (Li et al, 2011). Therefore, the relative high level of LCAT in obese subjects may be responsible for clearance of specific PC species.…”
Section: Added Value Of Metabolomics Analysismentioning
confidence: 99%
“…Furthermore, recently it was reported that LCAT-defi cient mice, especially females, are protected against high-fat high-sucrose (HFHS) dietinduced obesity ( 76 ). These protective metabolic phenotypes are associated with protection against diet-induced hepatic and adipocyte endoplasmic reticulum (ER) stress, but the mechanistic link with the enzymatic action of LCAT needs further investigation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Phosphatidylcholine-sterol acyltransferase or lecithincholesterol acyltransferase (LCAT) was up-modulated at 4 dpf, and it is a key enzyme in the intravascular metabolism of HDL cholesterol. 44 Importantly, cholesterol 25-hydroxylase (CH25H) was significantly up-modulated at 6 dpf, and it is thought to play a role in the inflammatory response because its expression is induced rapidly, selectively, and robustly by the TLR ligands poly I:C and LPS. [45][46][47][48] Transcriptome after mild (SLD) LPS treatment…”
Section: Dios Et Almentioning
confidence: 99%